Effects of fixed orthodontic appliances on subgingival microflora - M Ristic (Journal compilation 2008 Blackwell Munksgaard, 2008)
Fixed orthodontic appliances cause plaque accumulation around bands and brackets. Since the microbiological composition of dental plaque is closely connected to periodontal tissue health, the aim of this study was to determine the effects of fixed orthodontic appliances on subgingival microflora and periodontal status.